A carbon fiber / biomass-based sugar carbon aerogel high-efficiency thermal insulation material and its ionothermal preparation method

By combining carbon fiber pre-oxygen wire with biomass sugar carbon aerogel, the problems of low strength and high brittleness in the aerospace field are solved, and the synergistic effect of efficient heat insulation and toughening is achieved, providing technical support for its application in the aerospace field.

CN116675551BActive Publication Date: 2025-03-11HARBIN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310700008.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-14
Publication Date
2025-03-11
Estimated Expiration
2043-06-14

AI Technical Summary

Technical Problem

As a thermal insulation material, carbon aerogel has low strength, high brittleness, and pore structures are prone to deformation and failure under external forces, which limits its engineering application in the aerospace field.

Method used

Carbon fiber pre-oxygen wire is used to combine with biomass sugar carbon aerogel, and the space in the three-dimensional carbon fiber prefabricated body is filled with carbon aerogel, reducing solid heat conduction generated by fiber contact, and eliminating internal micro- and millimeter-level pores to reduce gas heat conduction.

Benefits of technology

It significantly improves the mechanical properties and low thermal conductivity of the material, improves its inherent brittleness, and realizes the coordination of efficient heat insulation and toughening, providing theoretical support for the application of carbon aerogel materials in the aerospace field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116675551B_ABST
    Figure CN116675551B_ABST
Patent Text Reader

Abstract

This application proposes a carbon fiber / biomass-based sugar carbon aerogel high-efficiency thermal insulation material and its ionothermal preparation method, which relates to the field of aerogel preparation. Carbon fiber pre-oxidized filaments are selected as reinforcing materials, and biomass sugar carbon aerogel is selected as the matrix material. The gas thermal conductivity of the fiber-reinforced aerogel thermal insulation material is very low, and the mechanical properties of the material can also be significantly improved. The carbon fiber / biomass-based sugar carbon aerogel prepared by the present invention not only ensures the low thermal conductivity of the carbon aerogel material, but also improves the mechanical properties of the aerogel material, improves its inherent brittleness, and realizes the synergy of high-efficiency thermal insulation and strengthening and toughening, providing theoretical support and technical reserves for the engineering application of carbon aerogel thermal insulation materials in aerospace vehicles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of aerogel preparation, and in particular to a carbon fiber / biomass-based sugar carbon aerogel high-efficiency thermal insulation material and an ionothermal preparation method thereof. Background Art

[0002] In recent years, with the advancement of aerospace technology and the increasingly complex international environment, hypersonic aircraft with faster speeds will have more initiative in wars, more rapid response time and stronger combat strike capabilities. Therefore, the United States, Russia and the European Union are actively developing new hypersonic aircraft technologies, and are accelerating. Since hypersonic aircraft need to maintain high-speed flight in the atmosphere for a long time, they will produce very high dynamic pressure and aerodynamic heating effects. The surface of the aircraft will be subjected to extremely large mechanical and thermal loads, and the surface temperature often reaches thousands of degrees, which also puts forward more stringent requirements on the thermal protection system. This requires that thermal protection materials need to be used stably in higher extreme temperatures, longer service time, and more severe thermal oxygen coupling environments, thereby protecting the precision components inside the aircraft from working safely at the allowable temperature. Therefore, there is an urgent need for efficient high-temperature resistant thermal insulation materials.

[0003] However, when used as a thermal insulation material, carbon aerogel has problems such as low strength, high brittleness, easy deformation and damage of the pore structure under external forces, and oxidation in an aerobic environment. This is also a bottleneck problem that restricts the further engineering application of carbon aerogel materials in the aerospace field.

[0004] The technical problem to be solved by the present invention is that carbon aerogel used as a thermal insulation material has low strength, high brittleness, and a pore structure that is easily deformed and damaged under the action of external forces, which restricts the further engineering application of carbon aerogel materials in the aerospace field. In order to overcome the deficiencies in the above-mentioned prior art, a low thermal conductivity, high strength and toughness carbon fiber / biomass-based sugar carbon aerogel high-efficiency thermal insulation material is provided. Summary of the invention

[0005] The purpose of the present application is to provide a carbon fiber / biomass-based sugar carbon aerogel high-efficiency thermal insulation material, which selects carbon fiber preoxidized filaments as reinforcing materials and biomass sugar carbon aerogel as matrix materials. In particular, after the carbon fiber preoxidized filaments are composited with the biomass sugar carbon aerogel, the heat transfer mode of the thermal insulation material will change significantly compared with ordinary aerogels. Since the space in the pores of the three-dimensional carbon fiber preform is filled with carbon aerogel, the contact between the fibers is isolated, thereby reducing the solid heat conduction generated by the fiber contact; the introduction of carbon aerogel will eliminate a large number of micron-level and millimeter-level pores existing inside the carbon fiber preform, and the gas heat conduction is mainly air heat conduction in the pores of the carbon aerogel, reducing the mutual collision between gas molecules, which leads to the low gas thermal conductivity of the fiber-reinforced aerogel thermal insulation material; after the carbon fiber preoxidized filaments are composited with the biomass sugar carbon aerogel, the mechanical properties of the material can also be significantly improved.

[0006] Another object of the present application is to provide a method for preparing a carbon fiber / biomass-based sugar carbon aerogel high-efficiency thermal insulation material. The carbon fiber / biomass-based sugar carbon aerogel prepared by the present invention can improve the mechanical properties of the aerogel material while ensuring the low thermal conductivity of the carbon aerogel material, improve its inherent brittleness, achieve the synergy of high-efficiency thermal insulation and strengthening, and provide theoretical support and technical reserves for the engineering application of carbon aerogel insulation materials in aerospace vehicles.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0008] On the one hand, an embodiment of the present application provides a carbon fiber / biomass-based sugar carbon aerogel high-efficiency thermal insulation material, comprising the following raw materials: 1-methylimidazole, 4-chloro-n-butyronitrile, fructose, and reinforced carbon fiber.

[0009] On the other hand, the present invention provides an ionothermal preparation method of a carbon fiber / biomass-based sugar carbon aerogel high-efficiency thermal insulation material, which comprises the following steps:

[0010] Step A: 4-chloro-n-butyronitrile and 1-methylimidazole are mixed and heated, and water is added to prepare [BCNmin]Cl ionic liquid for standby use;

[0011] Step B: mixing fructose and [BCNmin]Cl ionic liquid, and adding reinforced carbon fiber to prepare carbon fiber / biomass-based sugar carbon ionic liquid gel through hydrothermal reaction;

[0012] Step C: reflux-cleaning the prepared carbon fiber / biomass-based sugar carbon ion liquid gel in ethanol, then soaking it in tert-butanol, and freeze-drying it to obtain an uncarbonized carbon fiber / biomass-based sugar carbon aerogel;

[0013] Step D: Carbonizing the prepared carbon fiber / biomass-based sugar carbon aerogel at high temperature to obtain the final carbon fiber / biomass-based sugar carbon aerogel.

[0014] Compared with the prior art, the embodiments of the present application have at least the following advantages or beneficial effects:

[0015] The embodiment of the present application provides a carbon fiber / biomass-based sugar carbon aerogel high-efficiency thermal insulation material, which selects carbon fiber preoxidized filaments as reinforcing materials and biomass sugar carbon aerogel as matrix materials. In particular, after the carbon fiber preoxidized filaments are composited with the biomass sugar carbon aerogel, the heat transfer mode of the thermal insulation material will change significantly compared with ordinary aerogels. Since the space within the pores of the three-dimensional carbon fiber preform is filled with carbon aerogel, the contact between the fibers is isolated, thereby reducing the solid heat conduction generated by the fiber contact; the introduction of carbon aerogel will eliminate a large number of micron-level and millimeter-level pores inside the carbon fiber preform, and the gas heat conduction is mainly air heat conduction in the pores of the carbon aerogel, reducing the mutual collision between gas molecules, which results in the gas thermal conductivity of the fiber-reinforced aerogel thermal insulation material is also very low; after the carbon fiber preoxidized filaments are composited with the biomass sugar carbon aerogel, the mechanical properties of the material can also be significantly improved.

[0016] The embodiment of the present application provides an ionothermal preparation method for carbon fiber / biomass-based sugar carbon aerogel high-efficiency thermal insulation material. The carbon fiber / biomass-based sugar carbon aerogel prepared by the present invention not only ensures the low thermal conductivity of the carbon aerogel material, but also improves the mechanical properties of the aerogel material, improves its inherent brittleness, achieves the synergy of high-efficiency thermal insulation and strengthening, and provides theoretical support and technical reserves for the engineering application of carbon aerogel insulation materials in aerospace vehicles. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0018] Figure 1 The macroscopic morphology of the aerogel prepared in Example 1 of the present application;

[0019] Figure 2 This is a SEM image of the aerogel prepared in Example 1 of the present application;

[0020] Figure 3 This is a SEM image of the aerogel prepared in Example 2 of the present application;

[0021] Figure 4 This is a SEM image of the aerogel prepared in Example 3 of the present application;

[0022] Figure 5 This is the stress-strain curve of the aerogel prepared in Example 1 of the present application;

[0023] Figure 6 This is the stress-strain curve of the aerogel prepared in Example 2 of the present application;

[0024] Figure 7 This is the stress-strain curve of the aerogel prepared in Example 3 of the present application. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0026] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to specific embodiments.

[0027] The embodiment of the present application provides a carbon fiber / biomass-based sugar carbon aerogel high-efficiency thermal insulation material, comprising the following raw materials: 1-methylimidazole, 4-chloro-n-butyronitrile, fructose and reinforced carbon fiber.

[0028] Different from traditional materials, the carbon material used in this invention has a density of 1.8 g / cm 3) is significantly lower than that of metal materials and ceramic materials, and its mechanical properties are stable at high temperatures in an oxygen-free environment. Carbon aerogels (CAs) are a type of gas-solid two-phase material with a nanoporous network structure as the skeleton and gas as the dispersion medium uniformly filled in a three-dimensional porous network structure. Its porosity is as high as over 90%. At the same time, the pore size in the aerogel is generally in the mesoporous range of 2-50nm. Since the pore diameter of the aerogel is smaller than the mean free path of the gas molecules, most gas molecules can only collide with the skeleton, and the probability of gas molecule collision is very small, so the thermal conductivity is greatly limited. At the same time, the nanoporous structure separates the gas in countless tiny regional spaces, and it is difficult for the gas to convectively transfer heat, which leads to its extremely low thermal conductivity. Compared with traditional thermal insulation materials, carbon aerogel insulation materials with extremely low density have better thermal insulation effects while taking into account low thermal conductivity, lighter weight and smaller volume. The thermal physical properties of carbon aerogels do not decay in an oxygen-free environment at 2700℃, making it a new type of high-temperature and high-efficiency thermal insulation material. If carbon aerogel materials are used as components of the thermal protection system in aircraft, it can not only effectively reduce the thickness and mass of the thermal insulation components, but also increase the usable space in the aircraft cabin, which can greatly improve the application prospects of aerogel materials in military fields such as aviation and aerospace.

[0029] In some embodiments of the present application, the reinforced carbon fiber is any one of PAN pre-oxidized fibers, carbon nanofibers, and carbon nanotubes.

[0030] The present application provides an ionothermal preparation method of a carbon fiber / biomass-based sugar carbon aerogel high-efficiency thermal insulation material, which comprises the following steps:

[0031] Step A: 4-chloro-n-butyronitrile and 1-methylimidazole are mixed and heated, and water is added to prepare [BCNmin]Cl ionic liquid for standby use;

[0032] Step B: mixing fructose and [BCNmin]Cl ionic liquid, and adding reinforced carbon fiber to prepare carbon fiber / biomass-based sugar carbon ionic liquid gel through hydrothermal reaction;

[0033] Step C: The carbon fiber / biomass-based sugar carbon ion liquid gel prepared in step B is reflux-washed in ethanol, then soaked in tert-butanol, and freeze-dried to obtain an uncarbonized carbon fiber / biomass-based sugar carbon aerogel;

[0034] Step D: Carbonizing the carbon fiber / biomass-based sugar carbon aerogel prepared in step C at high temperature to obtain the final carbon fiber / biomass-based sugar carbon aerogel.

[0035] In step A, 4-chloro-n-butyronitrile and 1-methylimidazole react as follows:

[0036]

[0037] The ion thermal carbonization method is selected to prepare carbon fiber / biomass-based sugar carbon aerogel. The ion thermal carbonization method requires ionic liquid as the solvent of biomass. Ionic liquid is a liquid composed entirely of anions and cations. It is in liquid state between -100-200°C, has good thermal stability and low solvent volatility, and also plays an important role in the field of biomass-based carbon material synthesis. Ionic liquid can form hydrogen bonds with carbon sources to improve the solubility of biomass materials. Its acidity can accelerate the dehydration carbonization process of biomass such as fructose, reduce the generation of side reactions at high temperatures, effectively improve the carbon yield, and avoid the waste of raw materials. In addition, the ion thermal carbonization method can complete the carbonization process at a lower reaction temperature, which has certain advantages from the perspective of energy consumption. After the carbonization of biomass is completed, the ionic liquid will basically not be lost and can be reused after recovery and purification.

[0038] In some embodiments of the present application, in step A, 4-chlorobutyronitrile and 1-methylimidazole are mixed in a molar ratio of 1:1, and then kept at 60°C-90°C for 36h-48h, and the ratio of the mass of added water to the total mass of 4-chlorobutyronitrile and 1-methylimidazole is 100:6 to obtain [BCNmin]Cl ionic liquid.

[0039] In some embodiments of the present application, in step B, the mass ratio of fructose, [BCNmin]Cl ionic liquid, and reinforced carbon fiber is 4:12:(0.1-0.3).

[0040] In some embodiments of the present application, in step B, fructose and [BCNmin]Cl ionic liquid are mixed and added to reinforced carbon fiber, and then the mixed solution is added to a reactor, placed in an oven and heated to 120°C, kept warm for 3 hours, then heated to 180°C, kept warm for 6 hours, and taken out after cooling to obtain a carbon fiber / biomass-based sugar carbon ionic liquid gel.

[0041] In some embodiments of the present application, in step C, the ethanol reflux conditions are: 85°C-95°C for 24h-32h; the tert-butanol soaking time is 72h-96h, and the tert-butanol is replaced every 24h.

[0042] In some embodiments of the present application, in step D, the high-temperature carbonization conditions are: in a tubular furnace, the temperature is raised to 1000°C for 3 hours, kept at 1000°C for 2 hours, then cooled to 400°C for 3 hours, and then cooled naturally to finally complete the carbonization.

[0043] The features and performance of the present application are further described in detail below in conjunction with the embodiments.

[0044] Example 1

[0045] The present application provides an ionothermal preparation method of a carbon fiber / biomass-based sugar carbon aerogel high-efficiency thermal insulation material, which comprises the following steps:

[0046] Step A: 4-chloro-n-butyronitrile and 1-methylimidazole were mixed in a molar ratio of 1:1, and then sealed and kept warm in a DF101S heat-collecting constant temperature magnetic stirrer at 80°C in an oil bath for 48 hours. Figure 1 The reaction generates [BCNmin]Cl ion liquid. To improve the solubility of fructose in the [BCNmin]Cl ion liquid, water is added to the [BCNmin]Cl ion liquid at a mass ratio of 100:6 and set aside.

[0047] Step B: Weigh 4 g of fructose, 12 g of [BCNmin]Cl ionic liquid and 0.3 g of PAN pre-oxidized silk (diameter 10 μm, length 3 mm) and mix them evenly. Then put the mixed solution into a 25 ml reactor. After sealing the 25 ml reactor, place it in an oven and heat it at 120 ° C for 3 h, then heat it at 180 ° C for 6 h, take it out after cooling, and you can get the carbon fiber / biomass-based sugar carbon ionic liquid gel.

[0048] Step C: Use DF101S heat-collecting constant temperature magnetic stirrer to keep warm at 95°C, use ethanol to condense and reflux for 24 hours, repeatedly wash the carbon fiber / biomass-based sugar carbon ion liquid gel prepared in step B, replace the [BCNmin]Cl ion liquid in the gel pores, and then soak the carbon fiber / biomass-based sugar carbon ethanol gel with tert-butanol. Replace the tert-butanol every 24 hours for a total of 4 times to replace the ethanol in the gel pores. Then freeze the treated gel and place it in a vacuum freeze dryer for 24 hours to obtain uncarbonized carbon fiber / biomass-based sugar carbon aerogel.

[0049] Step D: The carbon fiber / biomass-based sugar carbon aerogel obtained in step C is placed in a tubular furnace, heated to 1000°C after 3 hours, kept at 1000°C for 2 hours, then cooled to 400°C for 3 hours, and then cooled naturally to finally complete carbonization to obtain a carbon fiber / biomass-based sugar carbon aerogel (such as Figure 1 and Figure 2 shown).

[0050] Example 2

[0051] The present application provides an ionothermal preparation method of a carbon fiber / biomass-based sugar carbon aerogel high-efficiency thermal insulation material, which comprises the following steps:

[0052] Step A: 4-chloro-n-butyronitrile and 1-methylimidazole were mixed in a molar ratio of 1:1, and then sealed and kept warm in a DF101S heat-collecting constant temperature magnetic stirrer at 80°C in an oil bath for 48 hours. Figure 1The reaction generates [BCNmin]Cl ion liquid. To improve the solubility of fructose in the [BCNmin]Cl ion liquid, water is added to the [BCNmin]Cl ion liquid at a mass ratio of 100:6 and set aside.

[0053] Step B: Weigh 4 g of fructose, 12 g of [BCNmin]Cl ionic liquid and 0.3 g of carbon nanofiber (diameter about 50 nm, length 10 μm), and mix them evenly. Then place the mixed solution in a 25 ml reactor. After sealing the 25 ml reactor, place it in an oven and heat it at 120 ° C for 3 h, then heat it at 180 ° C for 6 h, take it out after cooling, and you can get the carbon fiber / biomass-based sugar carbon ionic liquid gel.

[0054] Step C: Use DF101S heat-collecting constant temperature magnetic stirrer to keep warm at 95°C, use ethanol to condense and reflux for 24 hours, repeatedly wash the carbon fiber / biomass-based sugar carbon ion liquid gel prepared in step B, replace the [BCNmin]Cl ion liquid in the gel pores, and then soak the carbon fiber / biomass-based sugar carbon ethanol gel with tert-butanol. Replace the tert-butanol every 24 hours for a total of 4 times to replace the ethanol in the gel pores. Then freeze the treated gel and place it in a vacuum freeze dryer for 24 hours to obtain uncarbonized carbon fiber / biomass-based sugar carbon aerogel.

[0055] Step D: The carbon fiber / biomass-based sugar carbon aerogel obtained in step C is placed in a tubular furnace, heated to 1000°C after 3 hours, kept at 1000°C for 2 hours, then cooled to 400°C for 3 hours, and then cooled naturally to finally complete carbonization to obtain a carbon fiber / biomass-based sugar carbon aerogel (such as Figure 3 shown).

[0056] Example 3

[0057] The present application provides an ionothermal preparation method of a carbon fiber / biomass-based sugar carbon aerogel high-efficiency thermal insulation material, which comprises the following steps:

[0058] Step A: 4-chloro-n-butyronitrile and 1-methylimidazole were mixed in a molar ratio of 1:1, and then sealed and kept warm in a DF101S heat-collecting constant temperature magnetic stirrer at 80°C in an oil bath for 48 hours. Figure 1 The reaction generates [BCNmin]Cl ion liquid. To improve the solubility of fructose in the [BCNmin]Cl ion liquid, water is added to the [BCNmin]Cl ion liquid at a mass ratio of 100:6 and set aside.

[0059] Step B: Weigh 4 g of fructose, 12 g of [BCNmin]Cl ionic liquid and 0.3 g of multi-walled carbon nanotubes (diameter 5 nm, length 20 μm), and mix them evenly. Then place the mixed solution in a 25 ml reactor. After sealing the 25 ml reactor, place it in an oven and heat it at 120 ° C for 3 h, then heat it at 180 ° C for 6 h, take it out after cooling, and you can get a carbon fiber / biomass-based sugar carbon ionic liquid gel.

[0060] Step C: Use DF101S heat-collecting constant temperature magnetic stirrer to keep warm at 95°C, use ethanol to condense and reflux for 24 hours, repeatedly wash the carbon fiber / biomass-based sugar carbon ion liquid gel prepared in step B, replace the [BCNmin]Cl ion liquid in the gel pores, and then soak the carbon fiber / biomass-based sugar carbon ethanol gel with tert-butanol. Replace the tert-butanol every 24 hours for a total of 4 times to replace the ethanol in the gel pores. Then freeze the treated gel and place it in a vacuum freeze dryer for 24 hours to obtain uncarbonized carbon fiber / biomass-based sugar carbon aerogel.

[0061] Step D: The carbon fiber / biomass-based sugar carbon aerogel obtained in step C is placed in a tubular furnace, heated to 1000°C after 3 hours, kept at 1000°C for 2 hours, then cooled to 400°C for 3 hours, and then cooled naturally to finally complete carbonization to obtain a carbon fiber / biomass-based sugar carbon aerogel (such as Figure 4 shown).

[0062] Comparative Example

[0063] In this comparative example, a pure carbon aerogel is prepared. The steps of the preparation method are the same as those of Examples 1-3, except that no reinforcing carbon fibers are added.

[0064] Experimental example

[0065] The aerogels prepared in the comparative example and examples 1 to 3 were subjected to performance tests, including porosity, linear shrinkage, compressive strength and thermal conductivity. The specific performance test data are shown in Table 1:

[0066] Specific surface area analysis: Using N2 as the adsorption gas, 180°C and 1 h as the degassing temperature and degassing time, the BET specific surface area analysis of the fructose carbon aerogel block samples before and after carbonization prepared with the same parameters was performed to obtain the porosity data.

[0067] Compression performance test: The aerogels prepared in the comparative example and Examples 1-3 were cut and polished into cylindrical samples with a diameter of about 10 mm and a height of about 10 mm for uniaxial compression test. The samples were repeatedly tested at a compression rate of 0.2 mm / min using an Instron electronic universal testing machine to obtain compression strength data.

[0068] Thermal conductivity test: Under the conditions of an ambient temperature of 20° C., an ambient humidity of 45% RH, and an air atmosphere, the thermal conductivity of the aerogels prepared in the comparative example and Examples 1-3 was tested using a transient hot wire method.

[0069] Table 1. Performance test data

[0070]

[0071] As can be seen from the table above, PAN pre-oxidized fibers can significantly improve the mechanical properties of carbon aerogels. After adding reinforced carbon fibers, the compressive strength of carbon aerogels is increased to 2.455MPa, and the compression modulus is increased to 75.001MPa. At the same time, the introduction of PAN pre-oxidized fibers effectively reduces the intrinsic brittleness of carbon aerogels, and the enhanced carbon aerogels no longer have obvious brittle fractures. The introduction of PAN pre-oxidized fibers will improve the thermal conductivity of carbon aerogels to a certain extent.

[0072] In summary, the embodiment of the present application provides a carbon fiber / biomass-based sugar carbon aerogel high-efficiency thermal insulation material, which selects carbon fiber preoxidized filaments as reinforcing materials and biomass sugar carbon aerogel as matrix materials. In particular, after the carbon fiber preoxidized filaments are composited with the biomass sugar carbon aerogel, the heat transfer mode of the thermal insulation material will change significantly compared with ordinary aerogels. Since the space within the pores of the three-dimensional carbon fiber preform is filled with carbon aerogel, the contact between the fibers is isolated, thereby reducing the solid heat conduction generated by the fiber contact; the introduction of carbon aerogel will eliminate a large number of micron- and millimeter-level pores inside the carbon fiber preform, and the gas heat conduction is mainly air heat conduction in the pores of the carbon aerogel, reducing the mutual collision between gas molecules, which results in the gas thermal conductivity of the fiber-reinforced aerogel thermal insulation material is also very low; after the carbon fiber preoxidized filaments are composited with the biomass sugar carbon aerogel, the mechanical properties of the material can also be significantly improved.

[0073] The embodiment of the present application provides an ionothermal preparation method for carbon fiber / biomass-based sugar carbon aerogel high-efficiency thermal insulation material. The carbon fiber / biomass-based sugar carbon aerogel prepared by the present invention not only ensures the low thermal conductivity of the carbon aerogel material, but also improves the mechanical properties of the aerogel material, improves its inherent brittleness, achieves the synergy of high-efficiency thermal insulation and strengthening, and provides theoretical support and technical reserves for the engineering application of carbon aerogel insulation materials in aerospace vehicles.

[0074] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

Claims

1. A carbon fiber / biomass-based sugar carbon aerogel high-efficiency thermal insulation material, characterized in that: The invention comprises the following raw materials: 1-methylimidazole, 4-chloro-n-butyronitrile, fructose and reinforced carbon fiber; The ionothermal preparation method of the carbon fiber / biomass-based sugar carbon aerogel high-efficiency thermal insulation material comprises the following steps: Step A: 4-chloro-n-butyronitrile and 1-methylimidazole are mixed and heated, and water is added to prepare [BCNmin]Cl ionic liquid for standby use; Step B: Mix fructose and [BCNmin]Cl ionic liquid, add reinforced carbon fiber, and prepare carbon fiber / biomass-based sugar carbon ionic liquid gel by hydrothermal reaction; the hydrothermal reaction steps are: add the mixed solution into a reactor, place it in an oven and heat it to 120°C, keep it warm for 3 hours, then heat it to 180°C, keep it warm for 6 hours, take it out after cooling, and then obtain the carbon fiber / biomass-based sugar carbon ionic liquid gel; the reinforced carbon fiber is a carbon nanofiber with a diameter of 50nm and a length of 10μm; Step C: The carbon fiber / biomass-based sugar carbon ion liquid gel prepared in step B is reflux-washed in ethanol, then soaked in tert-butanol, and freeze-dried to obtain an uncarbonized carbon fiber / biomass-based sugar carbon aerogel; Step D: Carbonizing the carbon fiber / biomass-based sugar carbon aerogel prepared in step C at high temperature to obtain the final carbon fiber / biomass-based sugar carbon aerogel.

2. The carbon fiber / biomass-based sugar carbon aerogel high-efficiency thermal insulation material according to claim 1 is characterized in that: In the step A, 4-chlorobutyronitrile and 1-methylimidazole are mixed in a molar ratio of 1:1, and then kept at 60° C.-90° C. for 36 h-48 h, and the ratio of the mass of added water to the total mass of 4-chlorobutyronitrile and 1-methylimidazole is 100:6 to obtain [BCNmin]Cl ion liquid.

3. The carbon fiber / biomass-based sugar carbon aerogel high-efficiency thermal insulation material according to claim 1, characterized in that: In the step B, the mass ratio of fructose, [BCNmin]Cl ionic liquid and reinforced carbon fiber is 4:12:(0.1-0.3).

4. The carbon fiber / biomass-based sugar carbon aerogel high-efficiency thermal insulation material according to claim 1, characterized in that: In step C, the ethanol reflux condition is: at 85° C.-95° C. for 24 h-32 h; the tert-butanol soaking time is 72 h-96 h, and the tert-butanol is replaced every 24 h.

5. The carbon fiber / biomass-based sugar carbon aerogel high-efficiency thermal insulation material according to claim 1, characterized in that: In step D, the high temperature carbonization conditions are: in a tubular furnace, the temperature is raised to 1000° C. for 3 hours, kept at 1000° C. for 2 hours, then cooled to 400° C. for 3 hours, and then cooled naturally to finally complete the carbonization.